2018
DOI: 10.7717/peerj.4698
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal migrations, body temperature fluctuations, and infection dynamics in adult amphibians

Abstract: Risks of parasitism vary over time, with infection prevalence often fluctuating with seasonal changes in the annual cycle. Identifying the biological mechanisms underlying seasonality in infection can enable better prediction and prevention of future infection peaks. Obtaining longitudinal data on individual infections and traits across seasons throughout the annual cycle is perhaps the most effective means of achieving this aim, yet few studies have obtained such information for wildlife. Here, we tracked spi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 50 publications
0
31
0
Order By: Relevance
“…Further, the daily temperature maximum, minimum, and range of Yosemite toad breeding pools vary across elevational, latitudinal, and seasonal gradients [36], which may contribute to temporal and spatial patterns of Bd persistence in the environment or abundance on hosts. As such, understanding subtleties in the duration or intensity of exposure to temperatures above a pathogen's thermal optimum may be important in predicting disease in wild systems [15,23,46].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, the daily temperature maximum, minimum, and range of Yosemite toad breeding pools vary across elevational, latitudinal, and seasonal gradients [36], which may contribute to temporal and spatial patterns of Bd persistence in the environment or abundance on hosts. As such, understanding subtleties in the duration or intensity of exposure to temperatures above a pathogen's thermal optimum may be important in predicting disease in wild systems [15,23,46].…”
Section: Discussionmentioning
confidence: 99%
“…Differences in magnitude, range, and variability of temperature fluctuations affect host and pathogen traits in multiple disease systems [1,58]. Experiments that incorporate simulated natural temperature fluctuations, as opposed to temperature means, are likely to reveal important patterns in host and pathogen biology that may help identify potential climatic refugia or hotspots for infectious disease outbreaks [12,15,40,67]. Because temperature maxima and variability are projected to increase at daily and seasonal scales [17,47], it will be important to identify pathogen responses to larger and less predictable changes in temperature to better understand emerging infectious diseases in a changing climate.…”
Section: Discussionmentioning
confidence: 99%
“…Recovery of amphibian individuals both within and between seasons has been reported for several species of treefrogs Litoria spp. (Murray et al, 2009;Kinney et al, 2011;Sapsford et al, 2017) and spiny toads B. spinosus (Daversa et al, 2018). Reduced Bd prevalence between winter/spring and summer/autumn has also been shown for several amphibian species in Australia (Berger et al, 2004;Kriger & Hero, 2007) and North America (Voordouw et al, 2006;Duncan Pullen, Best & Ware, 2010).…”
Section: Introductionmentioning
confidence: 94%
“…Few studies have investigated the impact of Bd on amphibian movement, particularly in the case of wild animals. A laboratory study reported reduced peak speed of movement in Bdinfected leopard frogs Lithobates pipiens (Chatfield et al, 2013), while Daversa et al (2018) reported no effect on movement in four infected radio-tracked spiny toads, Bufo spinosus. Bd can also reduce the body condition in amphibians (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…First, migration can enable host recovery from infection (‘migratory recovery’; Daversa, Monsalve‐Carcaño, Carrascal, & Bosch, 2018; Shaw & Binning, 2016). This mechanism typically acts when host movement to a distinct environment increases the mortality of their parasites (Table 1).…”
Section: Introductionmentioning
confidence: 99%